PARTISIPASI PEMILIH TERHADAP PEMILIHAN GUBERNUR RIAU TAHUN 2013 BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2004 TENTANG PEMERINTAHAN DAERAH DI KOTA PEKANBARU - Joko '; Emilda Firdaus; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Political participation of the community is a hallmark of political modernization. Executive and legislative elections directly in Indonesia today also followed the local elections and the deputy head of the region mandated by Law No. 32 of 2004. The history of the arrangement of general elections in Indonesia showed the fact of the decrease voter turnout. This is evidenced by the declining number of voters in each election activities. The phenomenon of the decline and the lack of community participation in elections also occur at the local level (Pemilukada).The issues in this thesis is how voter participation in the election of Riau governor in 2013 in Pekanbaru City? What is the obtacle that affecting voter participation in election of Riau governor in 2013 in Pekanbaru city? And whether the efforts made to overcome the tendency of voter participation in the implementation of the election for Riau governor in 2013 in Pekanbaru city?This type of research can be classified as juridical empirical research, that is reviewing the state of the existing problems in the field and then associated with the applicable legal aspects done on location of the research by using data collection tools. The research was conducted including descriptive research that illustrates clearly and in detail and explain the reality of the field of voter participation based on law No. 32 of 2004 on the election of Riau governor in 2013 in Pekanbaru city. The conclusion of this research is the election governor in Pekanbaru city 2013 ago experienced a decline against the participation of voters in the first round where the amount of the participation only 53.37%. This election do in two-round election . Its effect on voter participation. In the second round of voter participation dropped to 46.4%. Pekanbaru city people's reluctance to participate on the election of the Riau governor in 2013, the crisis of public confidence of Pekanbaru city’s society towards the organizers the election of Riau governor in 2013, and the lack of socialization to the people of Pekanbaru city towards governor candidate in 2013 which became the obstacle. The efforts made by election commission (KPU) pekanbaru city related these obstacles is to improve the performance and role of volunteer teams democracy, maximizing dissemination and doing evaluation.Keywords: Elector’s participation, the election of Riau governor, the region government